How medical insurance payment systems affect the physicians’ provision behavior in China—based on experimental economics - Lin, Shuyan; Sun, Qiang; Zhou, Hezeng; Yin, Jia; Zheng, Chao (Frontiers in Public Health, 2024)
Background It introduced an artefactual field experiment to analyze the influence of incentives from fee-for-service (FFS) and diagnosis-intervention package (DIP) payments on physicians’ provision of medical services. Methods This study recruited 32 physicians from a national pilot city in China and utilized an artefactual field experiment to examine medical services provided to patients with different health status. Results In general, the average quantities of medical services provided by physicians under the FFS payment were higher than the optimal quantities, the difference was statistically significant. While the average quantities of medical services provided by physicians under the DIP payment were very close to the optimal quantities, the difference was not statistically significant. Physicians provided 24.49, 14.31 and 5.68% more medical services to patients with good, moderate and bad health status under the FFS payment than under the DIP payment. Patients with good, moderate and bad health status experienced corresponding losses of 5.70, 8.10 and 9.42% in benefits respectively under the DIP payment, the corresponding reductions in profits for physicians were 10.85, 20.85 and 35.51%. Conclusion It found patients are overserved under the FFS payment, but patients in bad health status can receive more adequate treatment. Physicians’ provision behavior can be regulated to a certain extent under the DIP payment and the DIP payment is suitable for the treatment of patients in relatively good health status. Doctors sometimes have violations under DIP payment, such as inadequate service and so on. Therefore, it is necessary to innovate the supervision of physicians’ provision behavior under the DIP payment. It showed both medical insurance payment systems and patients with difference health status can influence physicians’ provision behavior.